2021
DOI: 10.1002/ptr.7301
|View full text |Cite
|
Sign up to set email alerts
|

Rutaecarpine alleviates acute pancreatitis in mice and AR42J cells by suppressing the MAPK and NF‐κB signaling pathways via calcitonin gene‐related peptide

Abstract: Acute pancreatitis (AP) is an acute inflammatory condition of the pancreas. Previous studies have shown that rutaecarpine (RUT), an important alkaloid component of Evodia rutaecarpa, exhibits certain protective effects against AP in rats by upregulating calcitonin gene-related peptide (CGRP). However, the molecular mechanism of RUT in AP remains unknown. This study aimed to investigate the effects of RUT on ceruleininduced AP in vivo and in vitro, and to explore the underlying molecular mechanisms.In cerulein/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Rutaecarpine, an alkaloid extracted from the unripe fruit of E. rutaecarpa, possesses an antiinflammatory function [73]. Rutaecarpine has been reported to inhibit the expression of IL1B, IL6, and TNF and promote IL10 expression to ameliorate the histopathology damage caused by inflammation [74][75][76]. Baicalin, a flavonoid compound isolated from radix scutellariae, is characterized by its potent anti-inflammatory effect [77].…”
Section: Discussionmentioning
confidence: 99%
“…Rutaecarpine, an alkaloid extracted from the unripe fruit of E. rutaecarpa, possesses an antiinflammatory function [73]. Rutaecarpine has been reported to inhibit the expression of IL1B, IL6, and TNF and promote IL10 expression to ameliorate the histopathology damage caused by inflammation [74][75][76]. Baicalin, a flavonoid compound isolated from radix scutellariae, is characterized by its potent anti-inflammatory effect [77].…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory conditions like acute pancreatitis, TNFα, interleukins 3,6 are downregulated, and MAPK, NF-κB, and STAT3 signaling is inhibited in CGRP dependent manner. 57 Hence, we propose that further studies must be carried out after adjusting the confounders like age, gender, comorbidities and life style habits, with larger sample size will also add to the strength of the study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that rutaecarpine, a major alkaloid component of the Chinese herb Wu-Zhu-Yu (Evodia rutaecarpa), showed protective effects against NaTC-AP in mice, via promoting the release of CGRP ( Yan et al, 2018 ). Rutaecarpine was also found to inhibit tumor necrosis factor-α and IL-6 as well as upregulated IL-10 in CER/LPS-AP in mice ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%